2022
DOI: 10.3390/su14106186
|View full text |Cite
|
Sign up to set email alerts
|

Women on Boards in Portuguese Listed Companies: Does Gender Diversity Influence Financial Performance?

Abstract: Corporate sustainability integrates financial performance with environmental, social, and governance (ESG) performance. Due to their personal characteristics, women can play an important role in promoting sustainable actions and strategic decision-making, creating positive effects on a company’s financial performance. The main objective of this paper is to analyze the effect of Board gender diversity on financial performance, in the context of Portuguese listed companies. Financial performance was measured thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…These obstacles prevent women from advancing in their careers, and they are widespread in settings where men dominate and are the evaluators. Carmo et al (2022) studied BGD and firm performance in Portuguese-listed firms. He observed that firms with a minimum of 20% of representation of women on board showed higher performance.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…These obstacles prevent women from advancing in their careers, and they are widespread in settings where men dominate and are the evaluators. Carmo et al (2022) studied BGD and firm performance in Portuguese-listed firms. He observed that firms with a minimum of 20% of representation of women on board showed higher performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Carmo et al (2022) studied BGD and firm performance in Portuguese-listed firms. He observed that firms with a minimum of 20% of representation of women on board showed higher performance.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…ROA is the proxy used where it is the net income divided by total assets (Carmo et al, 2022;Gulamhussen & Santa, 2015). ROE assesses the firm's efficiency in generating profits and its return on shareholders' equity (Al-ahdal et al, 2020), and it denotes the returns on investment that a firm can cause (Maditinos et al, 2009).…”
Section: Independent Variable -Financial Performancementioning
confidence: 99%
“…We consider the institutional representativeness of women in three ways. First, if the firm has at least one WOB and 0; otherwise, a dummy variable is coded (1WOM) (Carmo et al, 2022). Second, the proportion of women on boards of directors (PWOM) is calculated by dividing the total of female directors by the total size of the board (Carmo et al, 2022;Eni-Egwu et al, 2022).…”
Section: Dependent Variableboard Gender Diversitymentioning
confidence: 99%